Have North-South Growth Linkages Changed? - Hoffmaister, Willy (IMF Working Papers; Working Paper, 1996)
This paper provides preliminary econometric evidence suggesting that the traditional trade-based business cycle linkages between the North and the South have changed. Many countries in the South, in particular in Asia, appear to have become more resilient to cyclical movements in the North, and to have come to play a more significant role in sustaining global activity, in particular during the 1991-93 slowdown. A number of factors may have contributed to these changes: improved domestic policies and more open trade and exchange regimes; closer financial linkages with the North and a substantial increase in capital flows; a marked rise in inter-regional trade; and greater diversification of the exports of the South.